TAFSIR SUFISTIK DALAM SIRAH NABAWIYAH: Analisis Teks al-Syifā’ karya al-Qāḍī Iyāḍ - Aulia Razmi, Arya (Academic Journal of Islamic Principles and Philosophy, 2025)
This study aims to analyze Sufistic interpretations in Sīrah Nabawīyah from the book al-Syifā' by al-Qāḍī ’Iyāḍ. The focus of the study is on the interpretation of the Qur'anic verses on the virtues of the Prophet Muhammad. This study is important because it reveals the Sufistic dimension that has received less attention in research on the interpretation and narration of Sīrah in al-Syifā'. The research method is qualitative based on a literature study, with data collection techniques through primary text analysis, namely al-Syifā' and secondary in the form of several Sufi tafsir books, as well as various authoritative books and articles. The findings of this study include: (1) al-Qāḍī ‘Iyāḍ not only quotes the Sufi interpretations of Sufi commentators such as al-Tustarī, al-Sulamī, al-Samarqandī, but also actively organizes them with the bi al-ma'ṡūr approach and the isyārī and naẓarī methods so that readers can directly receive the Sufistic meaning of the Sīrah through the narration of al-Syifā’. (2) Thus, al-Syifā' becomes an essential representation of the integration between normative and Sufistic interpretive traditions and enriches the discourse of Sufistic interpretation in the study of the Prophetic Sīrah, especially in the context of classical interpretation.